LIBER’s Involvement in Supporting Digital Preservation in Member Libraries - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
Digital curation and preservation represent new challenges for universities. LIBER has invested considerable effort to engage with the new agendas of digital preservation and digital curation. Through two successful phases of the LIFE project, LIBER is breaking new ground in identifying innovative models for costing digital curation and preservation. Through LIFE’s input into the US-UK Blue Ribbon Task Force on Sustainable Digital Preservation and Access, LIBER is aligned with major international work in the economics of digital preservation. In its emerging new strategy and structures, LIBER will continue to make substantial contributions in this area, mindful of the needs of European research libraries.